Diagnosis and repair of gypsum plaster coatings: statistical characterization and lessons learned from a field survey - Pereira, Ana; Palha, Filipe; Brito, Jorge de; Silvestre, José Dinis (Journal of Civil Engineering and Management, 2014)
This paper provides the statistical characterization of the pathological situation of 119 gypsum plaster coatings applied to partition walls and ceilings (inner gypsum plasters – IGP), the diagnosis methods that can be used to characterize the defects and confirm their causes, and the most suitable repair solutions. The results presented in this paper were achieved via the use of an expert system developed by the authors in an extensive inspection programme covering 23 buildings. A comprehensive set of charts and their detailed statistical analysis describe the results achieved, including the characteristics (temporal, spatial and severity) and frequency of the defects in the sample and the main causes of their occurrence in walls and ceilings. The most appropriate diagnosis methods, preventive measures and repair solutions prescribed for these defects in the sample are also analyzed and the most significant correlations presented. Even though in some instances the pathological situation of IGP is common knowledge, this time it has been characterized via quantitative indicators and using a statistically significant sample, which means that important lessons can be learned.